Socio-economic uncertainty and attitudes towards immigration in Europe - Martín Artiles, Antonio; Molina, Óscar; Meardi, Guglielmo (Cuadernos de Relaciones Laborales, 2013)
The recent economic crisis has brought an unprecedented deterioration in labour market conditions in many European countries. This may have provided new stimulus for the extension of anti-immigrant attitudes amongst population, especially amongst those in the lower segments of labour markets. In this paper we analyze the attitudes of European citizens towards immigration and migrant workers. In particular, we try to understand what role plays perceived socio-economic uncertainty in order to explain attitudes towards immigration. Comparing data of the 2002, 2008 y 2010 waves of European Social Survey for sixteen European countries, the paper shows no remarkable change in the relative importance of objective and subjective socio-economic variables between the period of growth and recession. Moreover, logistic analysis consistently shows political-ideology to be a strong predictor of attitudes. Finally, multiple correspondence analyses allowed us to classify the countries surveyed according to their attitudes towards immigration.